Pengetahuan Masyarakat Lokal Tentang Keragaman Teripang dan Pemanfaatannya di Pesisir Tablasupa, Depapre, Kabupaten Jayapura, Papua - Puguh Sujarta; Ervina Indrayani (Jurusan Biologi FMIPA Universitas Cenderawasih, 2016)
Sea cucumbers are organisms which have very important role in aquatic ecosystems as benthic biotas. The purpose of this study is to understand the public's knowledge about the diversity of sea cucumbers and its utilization in Tablasupa village. This study was conducted in May 2016, using a survey method by means of sampling and interviews. The results showed that based on the knowledge of local people, there are six species of sea cucumber. On the other hand, based on morphological identification, there were found eight species, which are Genus Actinopyga (2 types), Bohadschia (2 types), and Holothuria (6 types). Many people take advantage of the type of sea cucumbers for sale, and only a small portion is consumed. As a consequence of community activities is that increase the potential of reducing the species biodiversity of sea cucumber in the region. However, the existence of local knowledge management in this region is expected to reduce the loss of diversity and may improve the local environment ecosystem.Key words: benthic, ecosystems, Jayapura, Tablasupa, sea cucumbers